Prevalencia de cándida spp en cavidad oral de sujetos sanos. Revisión sistemática de la literatura (2021)
Opportunistic fungi of the genus Candida inhabit the oral cavity, they can colonize the mucous membranes being harmless yeasts or becoming pathogenic, depending on their association with the immune response or the presence of some risk factor.